Labor-management relations - Mills, Daniel Quinn (McGraw-Hill series in management, 1994)
The revision of this classic labor relations text, written by a respected scholar, emphasizes the rapid social, demographic, and economic changes now affecting the workplace. To this end, new chapters on workplace diversity and new work systems have been added. In addition, all material has been thoroughly updated, including important recent court decisions. The text continues to be distinguished by its comprehensive coverage and solid research base.